THEORETICAL FRAMEWORK FOR TEACHERS SELF- ASSESSMENT TO TEACH 21ST CENTURY SKILLS - Namsone, Dace; Čakāne, Līga; Eriņa, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The context of educational reforms taking place in many countries gives special relevance, as the curriculum enters the 21st century skills or so-called transversal skills. It is necessary to ascertain how successful the teaching of these skills is already so that the school management together with teachers develop evidence-based or data-driven professional development solutions. The aim of the research is to create a theoretical framework and corresponding self-assessment tools, how the teacher can assess for himself to what extent he has succeeded in achieving the competence to teach students in the 21st century skills required to achieve the goals set by the school in the context of the ongoing education reform in the country. For the self-assessment of teachers’ competencies, performance appraisal is used, comparing to what extent does teaching in a particular case correspond to good practice using performance level descriptors as tools - a set of teachers' learning progressions and tests. The developed set of teachers' professional learning progressions is based on data-based and field-tested analytical descriptions of performance levels from expert work. It includes 17 progressions developed within the framework of categories and criteria, the practical testing of which in school practice is planned in the authors' further research.